ARTEC—A furnace module for directional solidification and quenching experiments in microgravity - Balter, M.; Neumann, C.; Bräuer, D.; Dreißigacker, C.; Steinbach, S. (Review of scientific instruments, 2019)
A new experimental design for directional solidification experiments with high cooling rates under microgravity conditions is presented. The aerogel-based furnace module ARTEC (AeRogel TEchnology for Cast alloys) developed at DLR extends the earlier presented sounding rocket facility ARTEX by enabling a transition from low to high solidification velocities and a simultaneous operation of five independent furnaces in the same sounding rocket module. The furnaces for directional solidification are equipped with thermally insulating aerogels as a crucible material. Their optical transparency allows the control of the solidification parameters (velocity and temperature gradient) with optical methods in the lab. In ARTEC, a drastically increased solidification velocity is achieved by contacting the sample with a movable cooling-rod during processing. Therefore, a better theoretical understanding of the influence of a sudden change in solidification velocity on microstructure formation is obtained. Carrying out experiments in microgravity gives access to purely diffusive solidification conditions. Hence, convection free-growth can be compared with growth subject to natural (earth) and/or forced-convection (earth and space). Furthermore, alloys with high density differences in their alloy components and, hence, also between the primary solidifying phase and the surrounding liquid can be studied without the negative influence of fluid-flow or macrosegregation being present.